Optimizing the Use of Electronic Data Sources in Clinical Trials: The Landscape, Part 1. (November 2016) - Kellar, Ed; Bornstein, Susan M.; Caban, Aleny; Célingant, Catherine; Crouthamel, Michelle; Johnson, Chrissy; McIntire, Patricia A.; Milstead, Kenneth R.; Patterson, Jaclyn K.; Wilson, Brett
Background: TransCelerate BioPharma has created the eSource Initiative with the intent to facilitate the industry's movement toward optimal usage of electronic data sources. Although guidance and standards have been in place for some time, data collection methods and technology have not been utilized to their fullest capability, and transcription between electronic systems continues to be the norm. Methods: The TransCelerate approach for the eSource Initiative is to understand the current landscape and highlight factors that are influencing the adoption of new technologies. As a preliminary step in this process, TransCelerate surveyed member companies regarding eSource usage and barriers. Results: Literature review, stakeholder engagement, and the member survey have provided insight into the current landscape, which will help TransCelerate to develop proposals for best practices for industry utilization of electronic data collection tools and methods to benefit all stakeholders. Conclusions: Based on survey results, companies generally have taken steps to leverage current eSource technologies and prepare for optimal utilization of electronic data sources. The TransCelerate eSource Initiative will continue to evaluate the technology, regulatory, standards, and health care landscape to support the goal of improving global clinical science and global clinical trial execution. Forthcoming publications will focus on technology landscape, future vision, and demonstration projects.